Uptake of Pb2+ Using N-Vinyl Imidazole Based Uniform Porous Hydrogels - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (TAYLOR & FRANCIS INC, 2011)
The uniform porous and continuous phase lead (II) adsorbent hydrogel, was prepared by copolymerizing 2-hydroxyethyl methacrylate (HEMA), acrylic acid (AAc), and N,N'-methylenebisacrylamide (MBAAm), with n-vinyl imidazole (VIM). A series of hydrogels, including different ratios of VIM, were prepared by photopolymerization and characterized. The influence of the uptake conditions such as pH, functional monomer percent, contact time, initial feed concentration, and foreign metal ions on the metal ion binding capacity of hydrogel, were also tested. The selective chelation of heavy metal ions from synthetic wastewater was also studied. The affinity order on molar basis was observed as follows: Pb (II) > Zn (II) > Cd (II). Chelation behavior of heavy metal ions could be modelled using both the Langmuir and Freundlich isotherms and it was seen that the Langmuir isotherm model was the best fit for the adsorption of Pb (II) ions in P(VIM/AAc/HEMA) hydrogel. Moreover, the limits of detection and the quantification values were determined. Regeneration of the hydrogels was easily performed with 1M HCl and the same hydrogel can be reused five times almost without any loss of adsorption capacity. All these features make P(VIM/AAc/HEMA) hydrogels potential candidate adsorbent for heavy metal removal.
Keywords: N-vinyl imidazole; Pb (II) adsorption; Uniform porous hydrogel; UV curing; HEAVY-METAL IONS; AQUEOUS-SOLUTIONS; REMOVAL; WATER; ADSORPTION; BEADS; ACRYLAMIDE; MEMBRANES; CADMIUM; LEAD